ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PEMBELIAN IMPULSIF KONSUMEN DI PASAR MODERN KOTA TEGAL PADA MASA PANDEMI COVID-19 - Ardina Hermayanti (Monex: Journal of Accounting Research, 2022)
The role of retail trade which is packaged in the modern market is currently experiencing quite rapid development, however, with the Covid-19 pandemic, it has greatly impacted retail companies. The impact of the Covid-19 pandemic requires business actors and modern market managers to form strategies to develop and maintain the Balinese power of the community. The purpose of this study is to determine the magnitude of the influence of product completeness factors, price perceptions on impulsive purchases and motivation as intervening variables during the COVID-19 pandemic, on the other hand, to evaluate strategies in strengthening MSMEs in the city of Tegal. The object of this research is the modern market spread in the city of Tegal with a total sample of 150 respondents. This study uses the associative method. and analysis of data processing using the Partial Least Square – Structural Equation Modeling (PLS–SEM) method with data processing using Smart PLS. Then the outer model, inner model, and hypothesis testing were carried out. The results showed that the product completeness factor did not have a positive effect on consumer motivation, while price perceptions had a positive effect on consumer motivation. Product completeness, price perception and motivation have a positive effect on impulse buying. However, the motivational variable cannot mediate the relationship between product completeness and impulse buying at the modern market in the city of Tegal during the Covid-19 pandemic, while the price perception variable has a positive effect on impulse buying through consumer motivation in Tegal city modern market during the Covid-19 pandemic.